2023
DOI: 10.1371/journal.pone.0286112
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing in-service teachers’ technology integration model: Innovative strategies for educational technology

Ran Peng,
Rafiza Abdul Razak,
Siti Hajar Halili

Abstract: Technology invention and implementation have resulted in long-term educational progress. This study aimed to identify the innovative strategies in determining the factors influencing in-service teachers’ technology integration in China, focusing on the information and communication technology (ICT) integration. The sample consists of 685 in-service teachers. Four factors are found to influence in-service teachers’ ICT integration: attitudes, self-efficacy, digital competence, and digital tools use. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…However, according to Venkatesh et al (2003), self-efficacy does not directly influence the intention to use digital technology. This is supported by a study by Peng et al (2023), which found that self-efficacy influences IDT by mediating the effects of facilitating condition, such as digital tools. Hence, in this study, it was hypothesised that self-efficacy influences the IDT through the mediation of facilitating condition; furthermore, we also attempted to determine whether selfefficacy had any direct effects on the IDT.…”
Section: Self-efficacymentioning
confidence: 58%
See 1 more Smart Citation
“…However, according to Venkatesh et al (2003), self-efficacy does not directly influence the intention to use digital technology. This is supported by a study by Peng et al (2023), which found that self-efficacy influences IDT by mediating the effects of facilitating condition, such as digital tools. Hence, in this study, it was hypothesised that self-efficacy influences the IDT through the mediation of facilitating condition; furthermore, we also attempted to determine whether selfefficacy had any direct effects on the IDT.…”
Section: Self-efficacymentioning
confidence: 58%
“…To date, the extent to which teachers are integrating digital technologies in their teaching and the factors influencing their decisions in this matter have remained obscure (Fernández-Sánchez et al, 2022;Peng et al, 2023). There has been a paucity of empirical studies to explore the combined effects of such variables as self-efficacy, facilitating conditions or information and communication technology (ICT) infrastructure on the IDT in teaching (Kundu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, work in [20] argued that there exist several barriers for schools and other educational organisations to adopt e-learning within the workplace. In many schools, learning is still taking place within physical classrooms, and it is based on delivery methods, such as "sametime and same-place".…”
Section: Challenges Of E-learningmentioning
confidence: 99%
“…In many schools, learning is still taking place within physical classrooms, and it is based on delivery methods, such as "sametime and same-place". In these situations, [20] argued, teacher-centered approaches are the norm. Because the teachers work towards strict assessment requirements, they have a strict curriculum that needs to be followed in a step-by step fashion.…”
Section: Challenges Of E-learningmentioning
confidence: 99%
“…Research suggests that educators have not fully embraced technology due to skepticism and reluctance towards its use [14][15][16]. The integration of new technologies into teachers' instructional methods may face obstacles due to a range of challenges, including external factors such as insufficient support, a lack of essential technical resources, and curricular constraints, as well as internal factors like insufficient technical skills or low self-efficacy [17][18][19]. Research has also revealed that some educators prefer to use familiar resources and instructional methodologies and are frequently anxious about new technology, thus leading to their hesitance in technology adoption [20].…”
Section: Introductionmentioning
confidence: 99%